Criminal Liability Against Perpetrators of HOAX Spread in Indonesia - Rosyadi, Imron (International Journal of Law Dynamics Review, 2023)
The purpose of this article is to explain and examine the responsibility of perpetrators in the criminal act of disseminating information in the form of misleading fake news, especially based on Law Number 11 of 2008, let alone the blurring of norms related to the phrase fake and misleading news. One of the main problems of crime that occurs in society is the use of social media so the government needs to support the development of information technology through legal infrastructure and regulation so that the use of information technology must be carried out safely to prevent its misuse by taking into account the religious and socio-cultural values of the Indonesian people. This article is in the form of normative juridical research that is useful for finding solutions to legal issues that are the focus of study. The results showed that the perpetrators of spreading false news apply the principle "what must be proven is about the inability to be criminally responsible, and not about the ability to be criminally responsible" so that it can produce a fair legal decision as well as certainty and usefulness. If proven, the perpetrator can be sentenced based on the provisions in Article 28 paragraph (1) of the Electronic Information and Transaction Law with criminal threats based on Article 45A paragraph (1) of Law 19 Number 2016 with a maximum imprisonment of 6 (six) years and/or a maximum fine of IDR 1 billion.